THE CONTRIBUTION OF DETERMINERS TO ENGLISH SENTENCE STRUCTURE (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the syntactic functions of determiners in English, providing a comprehensive overview of their role in sentence construction. Determiners are identified as words that precede nouns to specify and modify them, and the article categorizes them into several types, including articles, demonstratives, possessives, quantifiers, and numbers. Each type of determiner is explained with examples, demonstrating how they contribute to marking definiteness, indicating quantity, showing possession, and establishing proximity. The article also outlines the typical syntactic structure of noun phrases, where determiners play a crucial role in establishing clarity and precision. Overall, the article emphasizes the importance of determiners in English grammar for effective communication and highlights their essential role in shaping the meaning of sentences